2014
DOI: 10.3389/fcimb.2014.00076
|View full text |Cite
|
Sign up to set email alerts
|

Forward genetic approaches for elucidation of novel regulators of Lyme arthritis severity

Abstract: Patients experiencing natural infection with Borrelia burgdorferi display a spectrum of associated symptoms and severity, strongly implicating the impact of genetically determined host factors in the pathogenesis of Lyme disease. Herein, we provide a summary of the host genetic factors that have been demonstrated to influence the severity and chronicity of Lyme arthritis symptoms, and a review of the resources available, current progress, and added value of a forward genetic approach for identification of nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…C3H/HeJ mice are susceptible to infection by Gram-negative bacteria as a result of spontaneous mutation in the Tlr4 gene (89). It has been demonstrated that C3H mice develop more severe arthritis and carditis following B. burgdorferi infection than B6 mice (90). B6 mice harbor tissue spirochete burdens equivalent to those of C3H mice, become persistently infected, and have normal macrophage function (89).…”
Section: Discussionmentioning
confidence: 99%
“…C3H/HeJ mice are susceptible to infection by Gram-negative bacteria as a result of spontaneous mutation in the Tlr4 gene (89). It has been demonstrated that C3H mice develop more severe arthritis and carditis following B. burgdorferi infection than B6 mice (90). B6 mice harbor tissue spirochete burdens equivalent to those of C3H mice, become persistently infected, and have normal macrophage function (89).…”
Section: Discussionmentioning
confidence: 99%
“…We previously identified an increased extracellular GAG deposition, visualized histochemically with Alcian blue staining, and localized inflammation following B. burgdorferi infection in severely Gusb deficient mice on a B6 genetic background ( Gusb Null ) and several Gusb hypomorphic strains (6, 10). The previously described runted growth and spontaneous rheumatologic abnormalities of Gusb Null mice suggest that the presence of excess partially degraded GAGs may be responsible for a shared disease process underlying both pathologies (11).…”
Section: Resultsmentioning
confidence: 99%
“…Pratt and Brown review the role of eicosanoids as important mediators of arthritis (Pratt and Brown, 2014 ). Also, Bramwell et al review the challenges of genome wide association studies for studying complex genetic traits in humans and the power of forward genetic approaches in model animals leading to the identification of genetic loci responsible for arthritis severity phenotypes (Bramwell et al, 2014 ). Finally, in a research paper, Belperron et al present data that implicate the FcRY receptor as an important contributor to acute phase Lyme arthritis (Belperron et al, 2014 ).…”
Section: Host Immunity—novel Pathways and Genetic Approachesmentioning
confidence: 99%